Research in Social Psychology Changed Between 2011 and 2016: Larger Sample Sizes, More Self-Report Measures, and More Online Studies. Issue 2 (June 2019) - Sassenberg, Kai; Ditrich, Lara
The debate about false positives in psychological research has led to a demand for higher statistical power. To meet this demand, researchers need to collect data from larger samples—which is important to increase replicability, but can be costly in both time and money (i.e., remuneration of participants). Given that researchers might need to compensate for these higher costs, we hypothesized that larger sample sizes might have been accompanied by more frequent use of less costly research methods (i.e., online data collection and self-report measures). To test this idea, we analyzed social psychology studies published in 2009, 2011, 2016, and 2018. Indeed, research reported in 2016 and 2018 (vs. 2009 and 2011) had larger sample sizes and relied more on online data collection and self-report measures. Thus, over these years, research improved in its statistical power, but also changed with regard to the methods applied. Implications for social psychology as a discipline are discussed.